Sarcopenia is linked to malnutrition among Palestinian patients aged >50 years admitted for elective surgeries, along with associated factors - Ali Shakhshir; May Hamdan; Islam Thaher; Nada Dweik; Ruba Abu Iram; Shurooq Osama; Manal Badrasawi (Journal of International Medical Research)
Objective This study aimed to evaluate the prevalence of sarcopenia and malnutrition among patients undergoing elective operations and the associated factors. Methods A cross-sectional study design was used to analyze data collected from 111 participants (60 males and 51 females) aged ≥50 years. The European Working Group on Sarcopenia in Older People criteria were used to define sarcopenia; anthropometric measurements, body composition data, and Mini Nutritional Assessment-Short Form questionnaire responses were used to assess the nutritional status of the participants. Results The prevalence rates of malnutrition and sarcopenia were 34% and 39%, respectively, in the study population. In addition, we found that malnourished patients were more likely to be female, unemployed, diabetic, and dyslipidemic. The study also showed that patients with sarcopenia were more likely to be older and have diabetes. Conclusions Malnutrition, diagnosed using the Mini Nutritional Assessment-Short Form questionnaire, is associated with sarcopenia, female sex, working condition, diabetes, and dyslipidemia. A significant association was reported between sarcopenia, age, and diabetes.